A COMPREENSÃO RESPONSIVA EM AULAS DE LEITURAS - The responsive understanding in reading classes (Revista Diálogos, 2017)
Neste artigo, apresentamos contribuições da compreensão responsiva para a construção do sentido nas aulas de leitura. O objetivo desse estudo é analisar a compreensão responsiva do aluno em aulas do conto e crônica no 9º ano. O corpus desse estudo é formado pela gravação de quatro aulas de leitura. Desses dados, selecionamos apenas fragmentos que interessam a análise. Os resultados mostram que as manifestações responsivas contribuem para o ensino da leitura da crônica, porém o professor (B) não obtém o mesmo efeito na abordagem do conto, pois suas estratégias do ato de ler ficam limitadas à significação literal das palavras.In this article, we present contributions of responsive understanding, Bakhtinian perspective, for the construction of meaning in reading classes. The objective of this study is to analyze the student's responsive comprehension in short stories classes in the 9th year of elementary school. The corpus of this study is formed by the recording of four reading classes. From these data, we only select fragments that are of interest to the analysis. The reasoning is mainly based on Bakhtin and the Circle and other authors who reflected on the Bakhtinian perspective. The results show that responsive manifestations contribute to the teaching of reading the chronicle, because teacher (A) uses dialogical strategies of sense construction, but teacher (B) does not have the same effect in approaching the story, because their strategies of reading are limited to the literal meaning of words.